2017
DOI: 10.1007/s12020-017-1377-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with hypoparathyroidism receiving standard treatment: a systematic review

Abstract: Most hypoparathyroidism patients receiving standard treatment show stable calcium and vitamin D levels. However, hypoparathyroidism patients still report reduced quality of life and experience physical, mental, and emotional symptoms. Therefore, it is assumed that the lack of parathyroid hormone directly influences the patients' quality of life. This review indicates that patients with hypoparathyroidism have a reduced quality of life in comparison to norm-based populations or matched controls. Further studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
79
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 32 publications
6
79
0
3
Order By: Relevance
“…An impairment of physical function as determined by QoL measures is in good agreement with many patients complaining of muscular symptoms, as well as studies have shown a reduced muscle strength/function compared with healthy controls [2]. As correctly noted by Büttner et al [1], conventional therapy with active vitamin D and calcium supplements does restore the physiological calcium/phosphorus homeostasis. In people with intact parathyroid function, serum calcium levels are tightly controlled.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…An impairment of physical function as determined by QoL measures is in good agreement with many patients complaining of muscular symptoms, as well as studies have shown a reduced muscle strength/function compared with healthy controls [2]. As correctly noted by Büttner et al [1], conventional therapy with active vitamin D and calcium supplements does restore the physiological calcium/phosphorus homeostasis. In people with intact parathyroid function, serum calcium levels are tightly controlled.…”
supporting
confidence: 70%
“…As many patients with non-surgical hypoparathyroidism have been born with the disease, it seems likely that patients who have acquired the diseases may feel more affected, as they know how they felt prior to being diseases. As reported by Büttner et al [1], most patients with postsurgical hypoparathyroidism are also suffering from postsurgical hypothyroidism. It may therefore be questioned whether the impaired QoL is due to the co-existence of hypothyroidism.…”
mentioning
confidence: 74%
See 3 more Smart Citations